Could effective communication lead toward active citizen participation? - Matkevičienė, Renata (Information & Media, 2017)
Review of Doctoral disseration “E-participation in the implementation of the third sector activities: case of Lithuanian non-governmental organizations” by Kristina Jakutytė-Ancienė